PENYEDIAAN FASILITAS UNTUK PEMAKAIAN HASIL-HASIL ASESMEN KEBUTUHAN PENDIDIKAN ISLAM - Muhammad Abdillah; Ahmad Salabi; Yahya Mof (PT. Hasba Edukasi Mandiri, 2026)
The provision of relevant facilities and infrastructure is a main pillar in supporting the quality and effectiveness of the learning process in Islamic educational institutions. However, the fulfillment of facilities is often carried out without careful planning, resulting in off-target allocation and budget inefficiency. This paper aims to analyze the strategy of providing educational facilities based on the utilization of needs assessment results, and to formulate implementation steps within the context of Islamic education. The method used in this study is library research with a qualitative-descriptive approach through critical analysis of various literatures on infrastructure management and educational planning. The results indicate that the systematic use of needs assessment results serves as a crucial database to minimize the gap between the actual condition of facilities and the expected ideal standards. An effective facility provision strategy must pass through the stages of identifying priority needs, drafting fulfillment action plans, allocating accountable budgets, to implementing transparent procurement. The practical implication of this study requires managers of Islamic educational institutions to substantively integrate assessment results into the Medium-Term Work Plan (RKJM) and Annual Work Plan (RKT) so that procurement of facilities can answer real academic needs and support the strengthening of the religious atmosphere of the institution in a sustainable manner.